An international patient-registry for primary ciliary dyskinesia - Werner, C.; Wallmeier, J.; Raidt, J.; Kuehni, C.; Leigh, M.; Yiallouros, Panayiotis K.; Lucas, J.; Lablans, M.; Ueckert, F.; Omran, H. (My University, 2014)
Introduction: Although rare in pediatric patients, endobronchial tumors can presentvarious pathologic patterns associated with partial or total airwayobstruction. Usually benign in infants, diagnosis and management of thesetumors remain challenging.Purpose:We report a case of capillary hemangioma of the left main bronchus,refractory to conventional medical therapy, in a young infant presentingwith persistent hyperlucency of the left hemithorax.Methods/Results:A 6 mo nth-old girl was referred to our institution for persistenthyperlucency of the left lung aft er recovery from left lower lobepneumonia. It is the second ch ild of a healthy non consanguine ousCaucasian couple, born after a full term pregnancy. She pr esented twoepisodes of left lower lobe pneumonia with upper lobe hyp erinflation at theages of 3 and 5 months. On admission, clinical examination revealed mildrespiratory distress including tach ypnea and hypoventilat ion of the lefthemithorax. The differenti al di agnosis included congenital lobar emphy-sema, endobronchial mass, extrinsic bronchial compression, Swyer-Jamessyndrome and foreign body aspiration. Bro nchoscopy showed completeobstruction of the left main bronchial lumen by a pulseless, vascularizedand depressible mass causing ai r trapping of the left lung. Computedtomography demonstrated an endobronchial well delimited mass of 5 mmdiameter in the left main bronchus with homogenous and positive contrastenhancement. Magnetic resonance imaging showed no gadolinium contrastenhancement and transoesopha geal pulsed doppler little or no measurableblood flow. Carcinoid tumor markers were not detected either in serum or inurine. The macroscopic aspect an d the young age of the patient being highlysuggestive of a benign hemangioma, treatment with cort icoids, propranololand acebutolol were consecutively attempt ed. As no reduction of the massvolume was observed by successive bronchoscop y, surgical resection andbronchial termino-terminal anastomosis were successfully conducted inorder to remove the mec hanical obstacle. An atomopat hology andimmuno histochemistry confirmed the diagnosis of capillary hemangioma.
Keywords: Primary ciliary dyskinesia; Delphi process; Epidemiological data